Transformasi Gang Sempit Menjadi Sentra UMKM: Model Pemberdayaan Masyarakat Go Global, Go Digital, Go Green di Kelurahan Duren Tiga - Rina Ekawati; Dadan Abdan Sakur (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
Narrow alleys in urban areas are often neglected despite their potential to be developed into productive economic spaces. This community service program aims to transform narrow alleys in Duren Tiga Village into UMKM centers implementing the concept of "go Global, go Digital, go Green" to increase beneficiary income and expand multi-stakeholder cooperation. The method used is a participatory approach based on social mapping, Café Mini Forest infrastructure development, capacity building through business skills training, product innovation, digital marketing, sanitation-hygiene, halal certification processes, and continuous mentoring. The program results demonstrate successful transformation of narrow alleys into productive community gathering and socializing spaces. Eight out of nine UMKMs successfully obtained halal certification, innovative product diversification based on passion fruit was created, digital marketing strategies were implemented through social media, and participation in the regional PERTIWI Exhibition Dekafy Fest 2025. The program successfully transformed the approach from charitable assistance to sustainable productive empowerment, although it has not yet changed the quality of life of beneficiaries completely and opens opportunities for future program development.